2002
DOI: 10.1016/s0304-3959(02)00268-3
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory amino acid receptor antagonists and electroacupuncture synergetically inhibit carrageenan-induced behavioral hyperalgesia and spinal fos expression in rats

Abstract: The interaction between electroacupuncture and an N-methyl-D-aspartic acid (NMDA) receptor antagonist, (DL-2-amino-5-phosphonopentanoic acid; AP5), or an (+/-)-alpha-Amino-3-hydroxy-5-methylisoxazole-4-propionic acid/kainite (AMPA/KA) receptor antagonist, (6,7-dinitroquinoxaline-2,3 (1H,4H); DNQX) administered intrathecally on carrageenan-induced thermal hyperalgesia and spinal c-Fos expression was investigated. The latency of paw withdrawal (PWL) from a thermal stimulus was used as a measure of hyperalgesia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…Acupoint Stimulator (LH-202H, Huawei Co., Ltd., Beijing, China). The electroacupuncture parameters were set as follows: square wave current output (pulse width: 0.2 ms); intensities ranging from 1-2-3 mA (each intensity for 10 min, totaling 30 min); at a 100 Hz and 2 Hz alternating frequencies (automatically shifting between 100 Hz and 2 Hz stimulation for three seconds each) (Zhang et al, 2002). Sham EA control animals received needle insertion into GB30 and GB34 similar to EA treatment, but without electrical stimulation.…”
Section: Electroacupuncture (Ea) Treatmentmentioning
confidence: 99%
“…Acupoint Stimulator (LH-202H, Huawei Co., Ltd., Beijing, China). The electroacupuncture parameters were set as follows: square wave current output (pulse width: 0.2 ms); intensities ranging from 1-2-3 mA (each intensity for 10 min, totaling 30 min); at a 100 Hz and 2 Hz alternating frequencies (automatically shifting between 100 Hz and 2 Hz stimulation for three seconds each) (Zhang et al, 2002). Sham EA control animals received needle insertion into GB30 and GB34 similar to EA treatment, but without electrical stimulation.…”
Section: Electroacupuncture (Ea) Treatmentmentioning
confidence: 99%
“…Recent chronic pain acupuncture/ electroacupuncture (EA) studies, including our own (Lao et al, 2004), have shown that EA produces anti-hyperalgesia in ankle sprain and inflammatory pain animal models (Koo et al, 2002;Zhang et al, 2002). Although our study *Corresponding author: Dr. Rui-Xin Zhang, Center for Integrative Medicine, University of Maryland, School of Medicine, HSF-2, Room S209, 20 Penn Street, Baltimore, MD 21201, Telephone: 410-706-1582, Fax: 410-706-1583, E-mail:Rzhan001@umaryland.edu.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture treatment reduces both the number of inflammatory cells and volume of exudate in several inflammatory models, such as carrageenan injection in the air pouch of rats, turpentine in rabbit ears, carrageenan-induced paw oedema, carrageenaninduced pleurisy, Freund's adjuvant-induced rheumatoid arthritis, sepsis and chemical peritonitis in rats (SIN et al, 1983;SIN, GWEE & LOH, 1984;SIN, 1986;KENDALL, 1989;QINGLAN, 1991;CECCHERELLI et al, 1999;KWON, et al, 2001;KWON, et al, 2002;ZHANG et al, 2002;SCOGNAMILLO-SZABÓ et al, 2004;SCOGNAMILLO-SZABÓ et al, 2004). Supporting these data, clinical trials confirm the efficacy of acupuncture treatment on allergic rhinitis, pruritic dermatosis, bronchial asthma, eczema, rheumatoid arthritis and other disorders (TOWNSEND et al, 1999;TUMACHI, 1999;CASIMIRO et al, 2002;PETTI et al, 2002;STEURER-STEYA;RUSSIB & STEURERC, 2002;BIELORY & HEIMALL, 2003;MADSEN et al, 2003;MCCARNEY et al, 2004).…”
Section: Introductionmentioning
confidence: 99%